Development of Human Resources in the Advanced Infrastructure Sector in Ciasmara Village, Pamijahan District, Bogor Regency - Wati, Lira; Budiono, Budiono; Sasmita, Agus; Wiranto, Puji (International Journal of Research in Community Services, 2024)
This Community Service (PkM) was motivated by the infrastructure problems of Ciasmara village with many roads damaged due to high rainfall and the village still using contractor services so that indirectly it had to spend more budget to pay for these services. This PkM activity is to provide knowledge and understanding to village officials about how to plan and calculate budgets regarding roads and bridges, heavy equipment used Autocad software, especially with regard to calculating the volume of each work item that has been prepared and will be implemented. The PkM implementation method goes through stages 1) Counseling, 2) Planning, 3) Training and 4) Evaluation. In this activity, village officials can have better insight, especially in terms of planning correct budget plans in accordance with existing (government) laws and regulations, especially those relating to government projects in particular and projects outside the government in general, so that in the future they will become reliable and capable village officials who will support the programs launched by Ciasmara village and provide better progress and contributions.